Populist Governments and the Quality of Governance: A Worldwide Comparison - Davide Grassi; Vincenzo Memoli; Ahmed Elshoura Abouzied (Partecipazione e Conflitto, 2022)
In spite of recent advances in the literature, there are still fewer empirical works, embracing different regions of the world, that analyze the impact of populist governments on the quality of governance. This paper, which covers 33 countries from five world regions from 1996 until 2019, intends to fill this gap. By using different statistical methods, our data show that periods under populist governments in power had a significantly negative effect on governance quality measured by the WGI data set. For each of the six dimensions of governance, however, (voice and accountability, political stability and the absence of violence, government effectiveness, regulatory quality, rule of law, and control of corruption) we detect exceptions. In addition, exploring the data by geographical region and types of populism (exclusive, neoliberal and inclusive), crucially refines our findings, showing a great deal of differences and revealing that similar types of populism operate in different ways in separate geographical contexts. These variations are explained both by the difficulty of defining slippery concepts, and applying them consistently to historical cases, and by particular traits and historical occurrences that significantly affect the relationship we analyze. Through different fixed regression models, finally, we control for a series of potentially confounding factors and find that our major descriptive findings have been confirmed.